2006
DOI: 10.1038/sj.npp.1301146
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abuse Liability of GHB in Humans: A Comparison of Psychomotor, Subjective, and Cognitive Effects of Supratherapeutic Doses of Triazolam, Pentobarbital, and GHB

Abstract: Although preclinical studies suggest that GHB has low likelihood for abuse, case reports indicate that GHB is abused. This study evaluated the relative abuse liability of GHB in 14 volunteers with histories of drug abuse. Psychomotor, subjective, and cognitive effects of a broad range of GHB doses (2-18 g/70 kg), up to a dose that produced severe behavioral impairment in each participant, were compared to placebo and two abused sedative/hypnotic drugs, triazolam (0.5 and 1 mg/70 kg) and pentobarbital (200 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 53 publications
6
65
2
1
Order By: Relevance
“…Benzodiazepine use has been associated with a wide range of cognitive side effects [46,77,78]. Few studies have compared SO and benzodiazepines on cognitive tasks [76][77][78][79], and due to differences in study populations and in cognitive tasks, the data of this study cannot be compared with Carter's data [76,79]. Nevertheless, the present results showed that sedation induced by SMO.IR remained mainly subjective and was less frequently observed in performance tasks.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Benzodiazepine use has been associated with a wide range of cognitive side effects [46,77,78]. Few studies have compared SO and benzodiazepines on cognitive tasks [76][77][78][79], and due to differences in study populations and in cognitive tasks, the data of this study cannot be compared with Carter's data [76,79]. Nevertheless, the present results showed that sedation induced by SMO.IR remained mainly subjective and was less frequently observed in performance tasks.…”
Section: Discussioncontrasting
confidence: 55%
“…First, the subjects had no history of alcohol use/abuse and therefore did not reflect the targeted population. However, in subjects with histories of abuse of sedative/hypnotic drugs, a great variability in sedation ratings was demonstrated [79] and most of them remained awake and alert after an administration of 2 or 4 g 70 kg -1 GHB. Moreover, only one dose of SMO.IR and one dose of alcohol were tested.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…In addition to covariates related to socio-demographics and co-occurring substance use, we included in our analysis independent variables related to anxiety and mood disorders (listed in the next section) since sedatives and tranquilizers have well-described anxiolytic effects (Carter et al, 2006;Helmus et al, 2005;Jackson et al, 2005;Zawertailo et al, 2003).…”
Section: Study Variablesmentioning
confidence: 99%
“…In rodent models, GHB caused acute impairment in working memory (Kueh et al 2008) and spatial learning (Pedraza et al 2009;Sircar et al 2008). GHB can also cause acute cognitive disturbance in human users, although this can be difficult to dissociate from the strong sedative effects of the drug (Carter et al 2006). To date, it is unclear whether there are lasting cognitive deficits arising from GHB use and addressing this issue was a major aim of the present study.…”
mentioning
confidence: 96%